Prevalence of diabetes in India: A review of IDF Diabetes Atlas 10th edition - Kumar, Arvind; Gangwar, Ruby; Ahmad Zargar, Abrar; Kumar, Ranjeet; Sharma, Amit (Current diabetes reviews, 2024)
Diabetes is a severe chronic disease that arises when insulin generation is insufficient, or the generated insulin cannot be used in the body, making it a long-term metabolic disorder. Diabetes affects an estimated 537 million adults worldwide between the age of 20 to 79 (10.5% of all adults in this age range). By 2030, 643 million people will have diabetes globally, increasing to 783 million by 2045. According to the IDF 10th edition, the incidence of diabetes has been rising in South-East Asia (SEA) nations for at least 20 years, and current estimates have outperformed all previous forecasts. This review aims to provide updated estimates and future projections of diabetes prevalence at the national and global levels by using data from the 10th edition of the IDF Diabetes Atlas 2021. For this review, we studied more than 60 previously published related articles from various sources, such as PubMed and Google Scholar, and we extracted 35 studies out of 60. however, we used only 34 studies directly related to diabetes and its prevalence at the global, SEA, and Indian levels. This review article concludes that in 2021 more than 1 in 10 adults worldwide developed diabetes. The estimated prevalence of diabetes in adults (20 to 79 years) has more than tripled since the first edition in 2000, rising from an estimated 151 million (4.6% of the world's population at the time) to 537.5 million (10.5%) of the world's population today. The prevalence rate will be higher than 12.8% by 2045. In addition, this study indicates that the incidence of diabetes in the world, Southeast Asia, and India was 10.5%, 8.8%, and 9.6%, respectively, throughout 2021 and will rise to 12.5%, 11.5%, and 10.9%, respectively by 2045.